2015
DOI: 10.1016/j.jana.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

“You're in a World of Chaos”: Experiences Accessing HIV Care and Adhering to Medications After Incarceration

Abstract: Most HIV-infected inmates leave prison with a suppressed viral load; many, however, become disconnected from care and non-adherent to medications during reentry to community life. In this secondary data analysis of focus groups (N = 6) and in-depth interviews (N = 9) with 46 formerly incarcerated HIV-infected people during reentry, we used an inductive analytic approach to explore the interplay between individual, interpersonal, community, and structural factors and HIV management. Participants described barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Correctional settings constitute an important setting for HIV care and treatment interventions as the receipt of HIV-related services during most recent incarceration was associated with DVS (2,5,6,14). The observed changes in viral suppression (i.e., baseline suppression of 44% and DVS of 20%) are consistent with previous studies that have shown HIV care and treatment benefit loss upon community release (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). As expected, medication adherence was critical for DVS such that participants who had achieved DVS were more likely to be adherent at baseline compared with both NVS and SVS participants.…”
Section: Changes In Viral Suppression and Correlates Of Dvssupporting
confidence: 87%
See 1 more Smart Citation
“…Correctional settings constitute an important setting for HIV care and treatment interventions as the receipt of HIV-related services during most recent incarceration was associated with DVS (2,5,6,14). The observed changes in viral suppression (i.e., baseline suppression of 44% and DVS of 20%) are consistent with previous studies that have shown HIV care and treatment benefit loss upon community release (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). As expected, medication adherence was critical for DVS such that participants who had achieved DVS were more likely to be adherent at baseline compared with both NVS and SVS participants.…”
Section: Changes In Viral Suppression and Correlates Of Dvssupporting
confidence: 87%
“…The post-release transition period is a vulnerable time for many CJI individuals living with HIV infection as the benefits of HIV treatment experienced during incarceration are frequently lost upon community re-entry (2)(3)(4)(5). Post-release HIV care visits and medication adherence become challenging due to a variety of co-occurring factors including limited income, high levels of unemployment, HIV stigma, mental health issues, and relapse to drug and alcohol use (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Such barriers have also been noted among CJI Black men who have sex with men (BMSM) living with HIV infection (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The overarching objective of the intervention was to maintain viral suppression following prison release, and entry into community medical care was presumed to be the critical mediator of this outcome. The intervention was finalized following formative research conducted with prison-based and community service providers as well as former inmates living with HIV infection, as has been previously reported (26, 27). The main elements of the tested intervention included the following:…”
Section: Methodsmentioning
confidence: 99%
“…The released prisoners face a lot of challenges when they reenter into the community which include substance abuse, stressful life experience, stigma, and discrimination in trying to fulfill the basic needs of life [26,27]. In such a situation, HIV care may get neglected.…”
Section: Discussionmentioning
confidence: 99%